PUBLIC SECTOR ACCOUNTING INFORMATION SYSTEMS AND THEIR IMPACT ON ORGANIZATIONAL PERFORMANCE - Kathleen Asyera Risakotta; Amiruddin Amiruddin; Asri Usman (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2026)
This study aims to analyze the role of public sector accounting information systems and their impact on organizational performance through a literature review approach. Accounting information systems in the public sector are a crucial instrument for increasing transparency, accountability, and efficiency in state financial management. In this study, various scientific literature sources, such as international journals, academic books, and research reports, were systematically analyzed to identify the relationship between the implementation of accounting information systems and improved organizational performance. The study results indicate that the effective implementation of accounting information systems can accelerate the decision-making process, improve the quality of financial reports, and support better internal control. Furthermore, factors such as human resource competence, technological support, and management commitment also influence the system's success in driving organizational performance. However, challenges such as limited infrastructure, resistance to change, and lack of training remain obstacles to optimizing accounting information systems in the public sector. Therefore, an integrative strategy is needed that includes strengthening human resource capacity, improving technology quality, and policies that support sustainable system implementation to achieve optimal organizational performance.